Education As Apprenticeship for Social Action: Composition Instruction, Critical Consciousness, and Engaged Pedagogy - David Alan Sapp (Networks: An Online Journal for Teacher Research, 2000)
As a professional teacher of writing, I see language as one of many locations in which political struggles exist, and the classroom as a site from which my students and I can actively examine culture, developing strategies of language-use that can facilitate social change. Critical and feminist pedagogies are two closely-related ways of teaching from which we can examine socially-created power structures so that society can move towards new ways of thinking and towards a new consciousness. The state of critical consciousness that results from these pedagogies becomes realized when students, studying as apprentices for social action, begin to speak out for the interests of groups of which they are members.